Impaired retrograde transport by the Dynein/Dynactin complex contributes to Tau-induced toxicity - Butzlaff, Malte; Hannan, Shabab B.; Karsten, Peter; Lenz, Sarah; Ng, Josephine; Voßfeldt, Hannes; Prüßing, Katja; Pflanz, Ralf; Schulz, Jörg B.; Rasse, Tobias M.; Voigt, Aaron (Human molecular genetics, 2015)
Abstract. The gene mapt codes for the microtubule-associated protein Tau. The R406W amino acid substitution in Tau is associated with frontotemporal dementia w